APPLICATION OF THE NUMBERED HEAD TOGETHER LEARNING MODEL TO STUDENT LEARNING OUTCOMES IN ACID BASE AND SALT MATERIALS IN CLASS VII SMP MIFTAHUL HUDA - Nur Riska Safitri; Rahmat Rasmawan; Maria Ulfah; Rachmat Sahputra; Risya Sasri (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to determine differences in student learning outcomes before and after being taught using the NHT learning model on acids, bases and salts for class VII SMP Mifathul Huda. This type of research is experimental research with the subjects of all seventh grade students of Miftahul Huda Middle School for the 2022/2023 academic year, totaling 12 students. The research design used was the Pre-experimental design of the One Group Pretest-Postest Design. The assessment instrument used is in the form of written test questions consisting of pretest and posttest questions which will be used to collect data. Based on the statistical analysis of student learning outcomes data using the Shapiro-Wilk test and the t test (Paired Sample T-test) yielded a Sig (2-tailed) value of 0.000 (<0.05) it can be concluded that there are differences in student learning outcomes before and after using the model NHT learning on acid-base and salt material for class VII SMP Miftahul Huda.